Effectiveness of Training Psychological Resilience on Aggression and Happiness among Students - Bahman Akbari (Guilan University of Medical Sciences, 2017)
Introduction: Today, psychological methods are being applied more often to reduce adverse effects of social life and to enhance positive and satisfying effects of communal life.One of these methods is psychological resilience training. Objective:The present study was conducted to determine the effectiveness of resilience training on aggression and happiness among nursing and midwifery students of Islamic Azad University of Rasht during 2013-14 academic years. Materials and Methods:This controlled quasi-experimental study with a pretest-posttest design used Oxford Happiness Questionnaire;Buss-Perry Aggression Scaleand Resilience Scale.The study population included 400 nursing students of Islamic Azad University of Rasht in the 2013-14 academic years. Inclusion criteria were willingness to participate in the study and no history of mental illnesses. Exclusion criteria were unwillingness to participate in the study, diagnosed psychological disorders, and the use of psychotropic medications and sedatives.According to the research methodology, the statistical sample consisted of 30 students selected using Morgan table by convenience sampling among eligible students who had low happiness score and high aggression score after completing the questionnaires. Then they were randomly assigned to the intervention and control groups (15 per group).The intervention group received twelve 75-minute sessions of resilience training by a consultant as a group and the control group received no training. After 12 sessions of resilience training, happiness and aggression among the students were measuredin both groups (post-test), and then the data were presented using descriptive statistics (mean, standard deviation).The covariance analysis was used to evaluate the effects of resilience components on happiness and aggression. Results:The statistical results showed that resilience training was effective on happiness and aggression reduction (P<0.001). According to the value of F and coefficient of Etta for the group variable and itssignificance in explaining the dependent variable of happiness, it could be said that resilience training was effective in increasing happiness.This difference was statistically significant at 1%. Conclusion: According to the findings, implementing resilience training programs can be effective in decreasing aggression and increasing happiness in students.Therefore, it is useful to add these programs to university curriculum.